O efeito da restrição de frutose artificial na dieta e a prática de exercício físico resistido sob os parâmetros antropométricos, bioquímicos e de qualidade de vida em indivíduos com esteatose hepática não alcoólica. - Freitas, Carolina Cristina de (2021)
Introduction: Non-alcoholic fatty liver disease is a manifestation of metabolic syndrome, characterized by the accumulation of fat on liver. The high consumption of fats, sugars and physical inactivity can lead to the progression of the disease. Studies indicate that fructose may be a carbohydrate with a high obesogenic potential when compared to other sugars, as its metabolism influences lipogenesis, which is the central abnormality of NAFLD. NAFLD is considered a preventable disease even when it reaches its advanced stages. Objective: evaluate the effect of artificial fructose restriction intake through food, resistance physical exercise under anthropometric, biochemical parameters and life quality in patients with steatosis. Methods: Interventional research, by 12 weeks, with patients with NAFLD, from 18 to 60 years old, who were divided into three groups: artificial fructose restricted diet (DF), resisted physical exercise (E) and artificial fructose restricted diet plus resistance exercise (DF + E). Results: 28 volunteer participants participated in the study (DF: 12, DF + E: 11, E: 5). The BMI showed a statistical difference between the groups (P: